Effect of Home Visit by Community Health Cadre on Postpartum Depression: Meta-Analysis - Hernanda R, Annisa Istighfari; Pamungkasari, Eti Poncorini; Prasetya, Hanung (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Postpartum depression is one of the most common mental disorders and complications of childbirth. Postpartum depression is associated with lower rates of initiation of breastfeeding, poorer mother-infant bonding, and an increase in infants exhibiting developmental delays. Efforts to prevent and treat postpartum depression can be done through home visits by community health cadres. This study aims to estimate and analyze the effect of home visits by community health cadres in reducing postpartum depression. Subjects and Method: This study was a systematic review and meta-analysis of the results of previous relevant research conducted using the PRISMA guidelines. The population included pregnant women and postpartum women, the intervention was given in the form of home visits by community health cadres with comparisons without home visits, and findings related to postpartum depression. Search for articles in this study through the PubMed, ScienceDirect, Scopus, and Google Scholar databases which were published between 2013-2023. The keywords used in the article search process were “home visit” AND (“community health worker” OR “lay health worker” OR “paraprofessional”) AND (“postpartum depression” OR “maternal depression”). The inclusion criteria for the articles included were full text articles and full papers with an RCT research design and including the Mean SD value. Findings from primary research articles were analyzed using the Review Manager 5.3 application. Results: The primary research included consisted of 9 articles from Tanzania, the United Kingdom, India, South Africa, the United States and Pakistan. The results of this meta-analysis showed that pregnant women and postpartum women who received home visits by community health cadres had an average postpartum depression rate of 0.27 units lower than mothers who did not receive home visits by community health cadres (SMD = -0.27; CI 95% = -0.52 to -0.03; p = 0.030). Conclusion: Home visits by community health cadres can reduce postpartum depression. Keywords: Home visits by community health cadres can reduce postpartum depression. Correspondence: Annisa Istighfari Hernanda. Master's Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java, Indonesia. Email: nnisa6173@gmail.com. Mobile: +6281335057080.